A ReaxFF-based molecular dynamics study of the oxidation decomposition mechanism of HFO-1336mzz(Z). (September 2018) - Huo, Erguang; Liu, Chao; Xu, Xiaoxiao; Li, Qibin; Dang, Chaobin
Highlights: The oxidation decomposition mechanism of HFO-1336mzz(Z) are first investigated. The initiation reactions of oxidation decomposition are detailed analyzed. O2 molecule attacks CC bond is more likely to occur in the initiation reactions. HF, COF2 and CO2 are the main products. Primary formation pathways of the main products are observed. Abstract: The oxidation decomposition mechanism of HFO-1336mzz(Z) were studied by ReaxFF simulations. The initial oxidation dissociation reactions of HFO-1336mzz(Z) can be divided into two types: thermal decomposition of HFO-1336mzz(Z) and the collision of O2 with HFO-1336mzz(Z). Most of the latter reactions are more likely to occur than the former ones. By comparing the energy barriers of initiation pathways, the pathway 2 and pathway 3 which involve the collision of CC bonds with O2 molecules are main reaction pathways and the energy barriers of these reactions are 153.3 and 135.3 kJ mol −1, respectively. HF, COF2 and CO2 are main products and the formation pathways of these products are observed from ReaxFF MD simulations. The main small radicals CF3, F, O, COF and COF3 play an important role in the oxidation decomposition of HFO-1336mzz(Z) because they can promote the decomposition of molecules and radicals and the formation of main products.